The Influence of Problem-Solving Skills and Self-Efficacy on Learning Outcomes in Skills Concentration Subjects - Suciati, Suciati; Sulistyowati, Raya; Suhartini, Ratna (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research is quantitative and aims to determine the impact of problem-solving skills and student self-efficacy on academic performance across various skill concentrations at SMK Negeri 1 Semen, Kediri Regency. The study focused on the subjects of Accounting (AKL), motorcycle engineering and business (TBSM), automotive light vehicle engineering (TKRO), and computer and network engineering (TKJ). Data collection involved questionnaires for assessing problem-solving skills and self-efficacy, while academic performance was measured through tests. The study included 185 students from all specialization concentrations at SMK Negeri 1 Semen, Kediri Regency. Data analysis utilized t-tests (partial test), f-tests (simultaneous test), and r2-tests or coefficient of determination tests. The research findings indicated that the significance level of the partial test for problem-solving skills was .002 < .050 and for self-efficacy was .003 < .050. The f-test revealed a significance value of .000 < .050. The results suggest that problem solving skills and self-efficacy significantly impact student academic performance across all skill concentrations, both individually and collectively.